Classroom Interventions and Foreign Language Anxiety: A Systematic Review With Narrative Approach - Toyama, Michiko; Yamazaki, Yoshitaka (Frontiers in Psychology, 2021)
Experimental studies have developed, conducted, and evaluated classroom interventions for foreign language anxiety reduction. However, various characteristics of those classroom interventions make it difficult to synthesize the findings and apply them to practice. We conducted what is, to the best of our knowledge, the first systematic review on educational interventions for foreign language anxiety. Six criteria were established for inclusion of studies. Using English keywords, we identified 854 potentially eligible studies through ProQuest and Scopus, 40 of which were finally included. All included studies were published from 2007 to 2020. The studies differed in type of intervention, duration of intervention, and scale to measure foreign language anxiety. Our systematic review resulted in seven features of classroom interventions, categorized as student-student interactions, student-teacher interactions, self-management, and mood boosters; we also categorized interventions as either individual or interactional.